The Role of Environmental Law in Preventing Environmental Degradation and Pollution - S.T. Kansil, Christine; Malkan, David Biliya (CV. Rayyan Dwi Bharata, 2024)
The damage that has occurred is very concerning and is often caused by human greed and negligence, which will impact future generations. This is a concerning situation and needs immediate special attention. One of the main causes of environmental problems is the lack of public awareness about the importance of environmental preservation. When individuals realize the importance of preserving and conserving the environment, they will be more prudent in utilizing natural resources. In Indonesia, sustainable development is defined as a planned effort that integrates the environment and resources into the development process, in order to ensure the welfare and quality of life for current and future generations. Regulation Number 32 of 2009 on Environmental Protection and Management (PPLH) clearly states that the environment is a spatial unit that includes all objects, forces, conditions, and living beings, including humans and their behavior, which affect nature, the survival, and well-being of humans and other living beings.